Environment and philosophy - Pratt, Vernon (Routledge, 2000)
Environment and Philosophy provides an accessible introduction to the radical challenges that environmentalism poses to concepts that have become almost second nature in the modern world. These include: * the ideas of science and objectivity * the conventional placement of the human being within the environment * the individualism of convential Modern thought Written in an accessible way for those without a background in philosophy, this text examines ways of thinking about ourselves, nature and our relationship with nature. It offers an introduction to the phenomenological perspective on environmental issues, and also to the questions of what natural beauty is.